Quick to Click How Metavoicing Affordance Leads to Instant Sharing of Fake News - Zohaib Riaz; Dr. Abid Saeed; Awan, Tahir Mumtaz (UW Journal of Management Sciences, 2024)
Objectives – Our study aims to examine the influence of social media metavoicing affordances (liking, commenting, sharing) on user behavior of the instant sharing of fake news. It studies the role of social media engagement, fake news self-efficacy, and perceived autonomy in shaping user response with fake news on social media platform. Methodology – we have conducted cross-sectional survey among 341 social media users in Pakistan. The data was collected through a structured online questionnaire. We used Partial Least Squares Structural Equation Modeling (PLS-SEM) for testing the hypothesis. For data analysis we have used smartPLS 4.0. Results – The study validates that metavoicing positively influences both social media engagement and the instant sharing of fake news. Social media engagement mediates this relationship, while fake news self-efficacy reduces impulsive sharing behavior. Perceived autonomy strengthens the connection between metavoicing and engagement. However, self-efficacy did not mediate the relationship between metavoicing, and instant sharing. Implications – The findings of our study suggested that social media platforms may design features to promote critical thinking and verification before sharing. Enhancing users' fake news self-efficacy and perceived autonomy could mitigate the rapid spread of fake News. Media literacy programs altered to contexts like Pakistan are also crucial in reducing the impact of fake news. Novelty – This research introduces fake news self-efficacy and perceived autonomy into the SOR framework to explain fake news dissemination. It also provides a unique focus on Pakistan, contributing valuable insights into the role of social media affordances in a developing country context. Key words: Metavoicing, Fake news, Self-efficacy, Social media engagement and Instant sharing.